A Physiological and Molecular Docking Insight on Quercetin Mediated Salinity Stress Tolerance in Chinese Flowering Cabbage and Increase in Glucosinolate Contents - Waheed Akram; Imran Khan; Areeba Rehman; Bareera Munir; Juxian Guo; Guihua Li (Plants, 2024)
The present study was performed to investigate the negative impact of salinity on the growth of Chinese flowering cabbage (Brassica rapa ssp. chinensis var. parachinensis) and the ameliorative effects of quercetin dihydrate on the plant along with the elucidation of underlying mechanisms. The tolerable NaCl stress level was initially screened for the Chinese flowering cabbage plants during a preliminary pot trial by exposing the plants to salinity levels (0, 50, 100, 150, 200, 250, 300, 350, and 400 mM) and 250 mM was adopted for further experimentation based on the findings. The greenhouse experiment was performed by adopting a completely randomized design using three different doses of quercetin dihydrate (50, 100, 150 µM) applied as a foliar treatment. The findings showed that the exposure salinity significantly reduced shoot length (46.5%), root length (21.2%), and dry biomass (32.1%) of Chinese flowering cabbage plants. Whereas, quercetin dihydrate applied at concentrations of 100, and 150 µM significantly diminished the effect of salinity stress by increasing shoot length (36.8- and 71.3%), root length (36.57- and 56.19%), dry biomass production (51.4- and 78.6%), Chl a (69.8- and 95.7%), Chl b (35.2- and 87.2%), and carotenoid contents (21.4- and 40.3%), respectively, compared to the plants cultivated in salinized conditions. The data of physiological parameters showed a significant effect of quercetin dihydrate on the activities of peroxidase, superoxide dismutase, and catalase enzymes. Interestingly, quercetin dihydrate increased the production of medicinally important glucosinolate compounds in Chinese flowering cabbage plants. Molecular docking analysis showed a strong affinity of quercetin dihydrate with three different stress-related proteins of B. rapa plants. Based on the findings, it could be concluded that quercetin dihydrate can increase the growth of Chinese flowering cabbage under both salinity and normal conditions, along with an increase in the medicinal quality of the plants. Further investigations are recommended as future perspectives using other abiotic stresses to declare quercetin dihydrate as an effective remedy to rescue plant growth under prevailing stress conditions.